Peningkatan kompetensi guru SMP Kristen Taaba melalui pelatihan Kurikulum Merdeka Belajar - Sole, Adriana I.S.; Pa, Hemi D. Bara; Boineno, Misael; Selan, Dominggus (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
The Independent Learning Curriculum is a new educational initiative in Indonesia aimed at producing high-quality education relevant to the evolving times. It emphasizes the development of students' potential, interests, social, emotional, and spiritual skills. This study focuses on implementing the Independent Learning Curriculum at SMP Kristen Taabah, Malaka District, with the objective of enhancing teachers' competencies in applying this curriculum. The training method used involved lectures and demonstrations. The activity was attended by 25 participants, consisting of 15 students and 10 teachers. The study results showed an increase in the understanding and readiness of teachers to implement the independent learning curriculum. Before training, teachers' understanding of the Independent Learning Curriculum was only 40%, which increased to 75% after training. Students also showed an increase in understanding, from initially 30% to 70% post-training. This activity successfully raised awareness and the ability of teachers to develop more creative and innovative learning approaches and strengthened students' understanding of the importance of education aligned with their interests and talents. The conclusion of this study emphasizes the importance of training and socialization in implementing the Independent Learning Curriculum, both for teachers and students, to achieve more effective and enjoyable educational goals